EKSPRESI CINTA PADA NOVEL â€œBIDADARI BIDADARI SURGAâ€ KARYA TERE-LIYE - Theresia Sri Susetianingsih (Jurusan Tadris Bahasa Indonesia, 2016)
The aims of the research are to describe and explain the characters love expressions in her novel â€œBidadari Bidadari Surgaâ€. The characters love expressions in the novel as an intense modal to develop the potencial in theirs family, the characters love expressions are as follows (a) giving love and secure feelings, (b) giving attentions to the family members, (c) building the nature behavior of the family members, and (d) giving the family identities.Â